Nursery.com Apps - Fauzi, Nur Hidayah; Mat Yusof, Sharmila (Multidisciplinary Applied Research and Innovation, 2023)
Nowadays, we can observe that the interests in gardening activities are increasingly popular among various age groups. Correspondingly, buying and selling gardening items such as plants, flowers, fertilizers, etc. by using online platforms is growing rapidly. However, most of the nursery stores are still selling their products using traditional method of physical store which limit the product marketing scope. Consequently, the nursery store cannot reach more customers especially those far from the stores which can increase their sales. In addition, customers are always not aware of the existence of the nursery stores that might offer good deals for them. Thus, the Nursery.com application is a one-stop platform for all nursery owners and customers in selling and buying nursery goods. The application allows customers to have more option in choosing and purchasing nursery goods from nursery stores that register with Nursery.com. This application would also enable nursery owners to market their products more effectively. The Nursery.com application was developed by adopting the Agile Development methodology. The benefit of the application for nursery owners is that Nursery.com application can serve as a platform that makes it easier for them to reach more customers in promoting their products. On the other hand, customers can have more option to compare and choose various nursery goods from the Nursery.com application.